EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RUMAH SAKIT “X” MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Nurul C, Aulia Riezky; Rimawati, Elistya (STMIK Sinar Nusantara, 2024)
During the implementation of SIMRS there are still some problems that occur such as incomplete features, there are still errors in the features accessed and still desktop-based. Therefore, researchers evaluate the Hospital Management Information System (SIMRS) based on user satisfaction and provide results in the form of recommendations for developing SIMRS. This research uses the End User Computing Satisfaction (EUCS) method which consists of 5 dimensions, namely Content, Accuracy, Display, User-Friendliness, and Timeliness. The data collection method is observation, interview, and distributing questionnaires to 125 SIMRS user employees using systematic random sampling techniques, the data is processed using SPSS version 23. The results showed that the level of satisfaction of “X” SIMRS users was 76.4%, which means that users are satisfied in using SIMRS and provide recommendations for improvements to SIMRS so that it can run well and user satisfaction continues to increase.